2011
DOI: 10.1631/jzus.b1100166
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma

Abstract: Abstract:Objective: To assess the clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma (EOC). Methods: A retrospective study of young EOC inpatients (≤40 years old) was performed during January 1994 and December 2010 in eight institutions. Results: Data were analyzed from 94 patients treated with fertility-sparing surgery with a median follow-up time of 58.7 months. As histologic grade increased, overall survival (OS) and disease-free survival (DFS) of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…A total of 15 studies [12,13,16,19,20,21,22,23,24,25,26,27,28,29,30] comprising 913 patients (11-43 years of age) met the inclusion criteria. In terms of assignability of recurrences to stage and grade, the cumulative analysis of data from 4 studies [13,20,22,30] published by Marpeau et al 2008 [31] contained more detailed information than some of the original publications and was therefore employed for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 15 studies [12,13,16,19,20,21,22,23,24,25,26,27,28,29,30] comprising 913 patients (11-43 years of age) met the inclusion criteria. In terms of assignability of recurrences to stage and grade, the cumulative analysis of data from 4 studies [13,20,22,30] published by Marpeau et al 2008 [31] contained more detailed information than some of the original publications and was therefore employed for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The tumor type distribution showed a substantial variation between studies (e.g. mucinous tumors ranging from 36.2% [28] to 76.2% [25]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies, including this review, fertility-sparing surgery has been defined as the preservation of ovarian tissue in one or both adnexa and the uterus in women of reproductive age [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39] (table 1). To date, 918 patients with EOC who underwent fertility-sparing surgery have been captured in the literature.…”
Section: Text Of Reviewmentioning
confidence: 99%
“…The safety of fertility-sparing surgery in women with stage IC and grade 3 EOC has not been determined, although the results of several recent series have suggested that fertility-sparing surgery is safe in patients with stage IC grade 1-2 EOC, regardless of the type of stage 1C (positive peritoneal cytology, capsule invasion or tumor rupture) [19,20,23,25,28,29,32,33,34,35,36,37,38,39]. Patients with preoperative or intraoperative tumor rupture, surface excrescences, or malignant cells in ascitic fluid or peritoneal washings are classified as having stage IC disease.…”
Section: Text Of Reviewmentioning
confidence: 99%